Les offrandes végétales dans l'Ancien Testament : du tribut d'hommage au repas eschatologique - Marx, Alfred. (Supplements to Vetus Testamentum,, 1994)
The present monograph is the first, since 1848, to be entirely devoted to the study of the cereal offerings. Its purpose is to attract attention to a form of sacrifice which was largely neglected and solely considered as an appendix to the animal sacrifice. The study of their substance, ritual and the circumstances in which the cereal offerings are brought to God demonstrates their great complexity as well as their specific function. His vegetarian utopia has led P to give the cereal offerings a prominent place among the sacrifices. A similar appreciation of the cereal offerings is also found among the Essenes, and, finally, in the Christian Last Supper.